Spatial distribution and core community of diazotrophs in Biological soil crusts and subsoils in temperate semi-arid and arid deserts of China - Tang, Kai; Liang, Yungang; Yuan, Bo; Meng, Jianyu; Feng, Fuying (Frontiers in Microbiology, 2023)
Introduction Biological soil crusts (BSCs) are distributed in arid and semiarid regions, and they function as important microhabitats for nitrogen fixation. The diazotroph community is critical for nitrogen fixation in BSCs and their subsoils. However, little is known about the key groups in different types of BSCs and subsoils in temperate semi-arid or arid deserts. Methods Here, we sampled three types of BSCs and their subsoils from the Inner Mongolian plateau, investigated the distribution characteristics of the diazotroph community by high-throughput sequencing, predicted keystone species using the molecular ecological network analyses pipeline (MENAP), and verified their close relationship with the available nitrogen (AN) content. Results The results showed that available nitrogen content in BSCs was higher than that in subsoils in three different types of BSCs, and there were differences among seasons and according to the mean annual precipitation. The abundance of diazotrophs was higher in Cyano-BSCs, while diversity had no significant difference among BSCs and subsoils. Cyanobacteria and Proteobacteria, Nostocaceae and Scytonemataceae, Skermanella, Scytonema, Azohydromonas, Nostoc and Trichormus were the dominant phyla, families, and genera, respectively. The dominant groups belong to Skermanella, Scytonema, and Nostoc formed the core diazotroph community in the three types of BSCs and subsoils, and each had a close relationship with AN. Discussion These results indicate that diazotrophs in BSCs and subsoils had high diversity, and the core diazotroph communities have a close relationship with nitrogen fixation and that they may be the main contributor to nitrogen fixing in BSCs and subsoils in temperate deserts.